Inventário urbano de Caçapava do Sul: patrimônio de valor arquitetônico, histórico e cultural - Morais, Michelle Campos (2013)
Due to the fact of knowing its past, the community must understand the necessity of knowing its patrimony, because it preserves its history. The architecture is one of the main manifestations for the analyses and understanding of the cities history, considering that the buildings are an important means of recognizing and urban reference. One should emphasize that it is essential, before any preservationist action, to identify and collect all the data regarding the patrimonial assets to be protected. The inventory control is also used as a preservation tool, which besides its documentation, is able to maintain the collective memory, providing respect and value of the assets. From that moment on, the result of this study refers to the patrimonial inventory of architectural, historical and cultural value, considering the updated registration of built examples in the urban area in the city of Caçapava do Sul. In 1987, an inventory of the city s assets was carried out, it was entitled as Caçapava Project , sixty-eight urban and thirty-nine rural properties were considered in it. In order to research about the present situation of such properties, the criterion of territorial delimitation was established with the purpose to select the properties to take inventory in the research. The Zone of patrimony s interest will be considered, according to the Municipal Development Master Plan, considering twenty-four properties listed in the inventory of 1987, taking into account that two assets were destroyed and twenty-two are remainders and will take inventory in the research. In conclusion, the intention is to collaborate concerning knowledge and dissemination for the community, rescuing the urban memory, encouraging the preservation and providing subsidies which may contribute substantially for the public policies and for the action plan in the areas of patrimony preservation in the city.